1974
DOI: 10.1111/j.1476-5381.1974.tb09629.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Prostaglandins in Rabbit Monoarticular Arthritis

Abstract: 1 Old English (OE) rabbits produced more severe monoarticular arthritis (MAA) after sensitization and intra-articular challenge with ovalbumin than did either New Zealand White (NZW) or Dutch rabbits. NZW rabbits were better responders than Dutch rabbits. 2 The swelling of the joint in all three strains of rabbits was triphasic. There was an initial acute swelling which appeared to peak at 2-4 days after challenge. This was followed by a decrease in joint size, and then a secondary increase in size beginning 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

1975
1975
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…As such an -experimental inflammation is promoted by endogenous inflammatory mediators including PGE2 (Willis, 1969;DiRosa et al 1971;Blackham et al 1974;Moncada et al 1975;Higgs & Salmon, 1979;Holsapple et al 1980;Higgs & Moncada, 1983) it may be assumed that these mediators also contribute to the sensitization of group III and IV units from inflamed joints. The present data show that PGE2 is able to induce a long-lasting increase of sensitivity to movements in group III units including some of those having a high threshold to movements in the control period.…”
Section: Discussionmentioning
confidence: 99%
“…As such an -experimental inflammation is promoted by endogenous inflammatory mediators including PGE2 (Willis, 1969;DiRosa et al 1971;Blackham et al 1974;Moncada et al 1975;Higgs & Salmon, 1979;Holsapple et al 1980;Higgs & Moncada, 1983) it may be assumed that these mediators also contribute to the sensitization of group III and IV units from inflamed joints. The present data show that PGE2 is able to induce a long-lasting increase of sensitivity to movements in group III units including some of those having a high threshold to movements in the control period.…”
Section: Discussionmentioning
confidence: 99%
“…Neural influences are known to be important, since it has been shown that electrical stimulation of sympathetic postganglionic fibres innervating the knee joint potently constricts articular blood vessels in the dog (Cobbold & Lewis, 1956), cat ) and rabbit (Ferrell & Najafipour, 1992), and that these exhibit vasoconstrictor 'tone' even in deeply anaesthetized animals (Cobbold & Lewis, 1956;. It has been shown that blood vessels in different species have the capacity to synthesize prostaglandins (Tuvemo & Wide, 1973;Aiken, 1974;Terragno, Crowshaw, Terragno & McGiff, 1975) and these agents change the vascular resistance (Blumberg, Denny, Marshall & Needleman, 1977) and modulate Although it is known that the synovial fluid from inflamed joints contains a high level of PGs (Blackham, Farmer, Radziwonik & Westwick, 1974; O'Byrne, Blancuzzi, Wilson, Wong, Peppard, Simke & Jeng, 1990), the role of these agents in regulation of blood flow and sympathetic vasoconstriction in normal and inflamed joints is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Prostaglandin E2 was also a potent vasodilator, approximately 5-10 times less potent than prostaglandin El. These results are of interest in that prostaglandin El is reported to be the main prostaglandin in the synovial fluid of inflamed joints both in experimental animals (Blackham et al, 1974) and in rheumatoid arthritis (Higgs et al, 1974).…”
Section: Discussionmentioning
confidence: 92%